PEMBENTUKAN KARAKTER RELIGIUS MELALUI PRAKTIK KEAGAMAAN DI SMK ROUDLATUT THULLAB BELITANG - Assyifa Nur Rahmadina; Marlina; Romdloni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low level of students’ religious character, which is reflected in discipline, responsibility, and moral behavior. Religious practices implemented in schools, such as Qur’an memorization (tahfiz), Friday charity programs, and Dhuha prayer, are considered strategic efforts to build students’ religious character; however, their effectiveness requires further investigation. This research aims to describe the formation of religious character through religious practices, analyze their implementation, and identify supporting and inhibiting factors at SMK Roudlatut Thullab Belitang. This study employs a qualitative approach with a descriptive method, using data collection techniques including interviews, observations, and documentation. The results indicate that the formation of religious character is carried out systematically through stages of planning, implementation, and evaluation. Religious activities such as tahfiz Al-Qur’an, congregational Dhuha prayer, and Friday charity are conducted regularly under teacher guidance. These practices are effective in fostering discipline, responsibility, patience, and social awareness among students. Supporting factors include school policies, the role of teachers, and a conducive religious environment, while inhibiting factors include students’ lack of consistency, differences in family background, and low motivation. Therefore, integrated and continuous religious practices play a significant role in shaping students’ religious character.